Peoples of the Inland Sea : Native Americans and Newcomers in the Great Lakes Region, 1600-1870 - Nichols, David Andrew, 1970- (New approaches to Midwestern studies., 2018)
"Diverse in their languages and customs, the Native American peoples of the Great Lakes region--the Miamis, Ho-Chunks, Potawatomis, Ojibwas, and many others--shared a tumultuous history. In the colonial era their rich homeland became a target of imperial ambition and an invasion zone for European diseases, technologies, beliefs, and colonists. Yet in the face of these challenges, their nations' strong bonds of trade, intermarriage, and association grew and extended throughout their watery domain, and strategic relationships and choices allowed them to survive in an era of war, epidemic, and invasion. In Peoples of the Inland Sea, David Andrew Nichols offers a fresh and boundary-crossing history of the Lakes peoples over nearly three centuries of rapid change, from pre-Columbian times through the era of Andrew Jackson's Removal program. As the people themselves persisted, so did their customs, religions, and control over their destinies, even in the Removal era. In Nichols' hands, Native, French, American, and English sources combine to to tell this important story in a way as imaginative as it is bold. Accessible and creative, Peoples of the Inland Sea is destined to become a classroom staple and a classic in Native American history"--